Penerapan Nilai-Nilai Tafsir Tarbawi Dalam Kegiatan Belajar Mengajar: Meneladani Strategi Pendidikan Rasulullah SAW - Haq, Ihsan Abdul (Mustaneer : Journal of Islamic Thought and Civilization, 2025)
This study aims to examine the urgency and relevance of applying Tarbawi Interpretation values in the teaching and learning process (KBM), by emulating the educational strategies implemented by the Prophet Muhammad SAW. This study employs a qualitative-descriptive approach, utilizing literature analysis and observations of KBM practices in Islamic educational institutions, to explore the concrete forms of integrating Tafsir Tarbawi into pedagogical practices. The findings indicate that Tafsir Tarbawi, as an approach to interpreting the Quran that focuses on educational values and character development, makes a significant contribution to building a learning system that is not only cognitive but also affective and spiritual. By adopting the holistic, dialogical, and exemplary (uswah hasanah) educational methods of the Prophet Muhammad SAW, KBM is expected to create a more meaningful learning process, shape students with noble character, and instill Qur’anic values in daily life. The implementation of Tafsir Tarbawi values can revitalize the role of teachers as spiritual and intellectual educators, while also positioning the Qur’an as the primary source for character development and competency building among students in the contemporary era.